Representasi Kebebasan Identitas pada Video Klip Lagu Montero (Call Me By Your Name) dalam Perspektif Ajaran Islam - Amara Putri Pertiwi; Arvindhia Nadhief Zaidan; Budi Rizky Rabbani; Dadan Dadan; Maulida Azzahra (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the representation of identity freedom in Lil Nas X’s music vudeo Montero (Call Me By Your Name) from an Islamic theological persektive. Using Roland Barthes’s semiotic analysis, the study finds that the music video radically deconstructs religious symbols to contruct a myth of absolute individual freedom over queer identity. From Islamic theology (Kalam) and jurisprudence (Fiqh) viewpoits, this concept contradicts human nature as a servant of God and violates tasyabbuh prohibitins. This digital culture shift triggers intellectual syiruk khafi and digital riya’ among students. Although students display Karl Popper’s critical epistemology, reinforcing digital literacy based on Tawhid values remains crucial.